Internationalization of Chinese manufacturing firms: a perspective from the Uppsala model - Huang, Jianhong; Raja Yusof, Raja Nerina; Abd Rahman, Azmawani; Ab Rahman, Rozanah (Canadian Center of Science and Education, 2024)
Enhancing firm performance in the turbulent international situation has become an important issue in firm evolution. There has been a large amount of research interest in the rapid development of emerging international firms, but the relevant empirical studies are still limited. The purpose of this study is to investigate three factors that impact firm performance, utilizing the Uppsala model as a main theoretical foundation. Based on empirical analysis of 332 medium and large Chinese manufacturing international firms, this study finds that the degree of internationalization, knowledge development, and commitment processes have positively impact firm performance. This finding contributes to the international business literature's understanding of firm development in emerging markets and enhances the generalizability of the Uppsala model.